STAFF TRAINING FOR SERVICE INDUSTRY (Journal of Information Technologies in Education (ITE), 2015)
In all countries across the world macroeconomic shift from the production of physical things (agriculture and manufactured goods) to execution of the service of public service. In headmost countries more than 70% of GDP forms by service industry, in which over half of mankind is working today (according to the information of International Labor Organization). The science of services that occurred recently upon an initiative of IBM firm, designed to explore the main principles of functioning complex services systems, ways of creation, scaling and improving such systems. In this paper considered the questions of penetration the services in engineering systems (particularly, in software structures) capabilities of the engineering and staffing processes of creating and maintaining of system services.
Keywords: the science of services; SSME; service engineering; system services; Web services; business process; problem streams; system services design; service engineer